Determining the Effect of Spirituality and Cultural Intelligence on Emotional Intelligence of Female Scholars in the Seminary of Fatemeh Al-Zahra of Sari City in the Academic Year 2017-2018 - vakili, Khatoon; Farhadi Bazmin Abadi, Sareh; Zoleykani, Azam (International Journal of Engineering and Technology, 2018)
The purpose of this study is to determine the effect of spirituality and cultural intelligence on emotional intelligence of female scholars of the Seminary of Fatemeh Al-Zahra of Sari city in the academic year 2017-2018. The research methods are descriptive, survey and correlation. The statistical population includes all the female scholars of the Seminary of Fatemeh Al-Zahra of Sari. A total of 80 subjects were selected. The Likert scale was used for data collection. To analyze the data by SPSS software and test the research hypotheses, we used inferential statistics and structured equation modeling method using the LISER software. The results of the study showed that there is a significant relationship between reliance on inner being and cultural intelligence, and there is also a relationship between understanding and communication with the origin of existence and cultural intelligence. There is also a significant relationship between emotional intelligence and cultural intelligence.Â Â